1992
DOI: 10.1002/j.1460-2075.1992.tb05092.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin VH clan and family identity predicts variable domain structure and may influence antigen binding.

Abstract: Mammalian immunoglobulin VH families can be grouped into three distinct clans based upon sequence conservation in two of the three framework (FR) intervals. Through replacement/silent site substitution analysis, molecular modeling and mathematical evaluation of known immunoglobulin crystal structures, we demonstrate that this conservation reflects preservation of protein sequence and structure. Each clan contains a characteristic FR 1 interval that is solvent‐exposed and structurally separated from the antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(83 citation statements)
references
References 34 publications
3
80
0
Order By: Relevance
“…By contrast, the phylogenetic classification of tetrapod IGHV sequences into three clans (I, II, and III) is clearly supported by high (>75%) bootstrap values. These three clans are equivalent to the clans I, II, and III reported previously for the phylogenetic classification of mammalian IGHV sequences (Kirkham et al 1992;Schroeder et al 1990). The presence of all three clans in the frog Xenopus (Fig.…”
Section: Phylogenetic Relationships Of Ighv Genes In Vertebratessupporting
confidence: 78%
See 1 more Smart Citation
“…By contrast, the phylogenetic classification of tetrapod IGHV sequences into three clans (I, II, and III) is clearly supported by high (>75%) bootstrap values. These three clans are equivalent to the clans I, II, and III reported previously for the phylogenetic classification of mammalian IGHV sequences (Kirkham et al 1992;Schroeder et al 1990). The presence of all three clans in the frog Xenopus (Fig.…”
Section: Phylogenetic Relationships Of Ighv Genes In Vertebratessupporting
confidence: 78%
“…On the basis of the degree of sequence identity, mammalian IGHV genes have been classified into three major clans (clans I-III) (Kirkham et al 1992;Kodaira et al 1986;Kofler et al 1992;Ota and Nei 1994;Schroeder et al 1990). The number of IGHV genes in these three clans varies among different mammals (Sitnikova and Su 1998).…”
Section: Introductionmentioning
confidence: 99%
“…During this stage of differentiation, interactions with self antigens could lead to positive or negative selection of B cells expressing specific V H germline gene products (4,5). As pairing of H chains with L chain is thought to mask availability of the CDR3 (6), selection at this stage of B cell maturation is proposed to relate largely to the nature of the V H segment expressed. In the mouse, selection of the Ig repertoire based on V H expression has been suggested to occur (7).…”
Section: Introductionmentioning
confidence: 99%
“…This finding, together with the observation that fish V H sequences have their closest homologs in mammalian clan III sequences, led to the assumption that this is the most ancient of the three mammalian clans (5,(12)(13)(14)(15). However, more recent data have shown that both cow (Bos taurus) and sheep express only one V H gene family, which belongs to clan II (16 -19).…”
mentioning
confidence: 99%